Effect of Electromagnetic Field (ELF) on Humanʹs Body-Review - Farhan, Ahmed Mohammed; Farhan, Hadeer Mohammed (Journal of engineering sciences and information technology, 2023)
This study analyzed and showed the effects of electromagnetic fields on humans (current studies have shown that using a mobile phone for six hours or more each day for five days in a row causes sexual failure in the body). Frequency, wavelength, and energy are the three fundamental components of electromagnetic waves, which are short-range waves that occur from the oscillation of the electric field and the magnetic field. Additionally, non-ionizing radiation can be regarded of as the magnetic field. This argues that this is because microwaves, cell towers, and other source of radiation are less toxic than ionizing radiation, they do not represent ionizing radiation. The high frequency has to have an impact on health because the wavelength is lower than the diameter of living cells, resulting in a consequence on the cell nucleus. Recent research demonstrates that a range of factors, such as the long - term exposure, exposing the organism to absorbing electricity energy, and increasing vibrations from x-rays and nuclear radiation, raise the body’s exposure to electromagnetic waves.